Comparative Study of the Authority of the MPR During the New Order and Reform Order from the Perspective of the Theory of Dignified Justice - Franciscus Xaverius Wartoyo (International Journal of Educational Research Excellence (IJERE), 2023)
"Sovereignty is in the hands of the people and is implemented according to the Constitution." Paragraph 2 of Article 1 of the 1945 Constitution asserts that the sovereignty of citizens must be defended through constitutional law. Sovereign people do not mean freedom to act arbitrarily either in actions or in providing aspirations for the interests of citizens in an authoritarian manner but in the form of consensus deliberation in institutions. The formation of rules for implementing the authority of the MPR institution is deemed necessary to be regulated in a separate law, outside of "Law no. 17” of 2017 concerning MD3, considering that the MPR has fundamental authority and is the sole implementer of popular sovereignty. This is different from people's representative institutions such as the DPR, DPD and DPRD. Regulations or legislation for the special authority of the MPR outside "Law no. 17 of 2017” About MD3. So as not to give rise to interpretations that have similar authority. This formation is intended to carry out none other than the goals of the nation, based on state philosophy and the unique values of the Indonesian nation in accordance with the philosophy contained in the 4th paragraph of the Preamble to the 1945 Constitution of the Republic of Indonesia and the 4th principle of Pancasila. So it can be concluded that in regulating the authority of the MPR it is necessary to create a special law/special authority that regulates the MPR so that the function of the MPR can be optimal in making policies but still listening to the aspirations of the DPD, DPR, DPRD, and the wider community who are members of skilled professions such as academics, and other professions related to this authority.